2022
DOI: 10.1111/sode.12631
|View full text |Cite
|
Sign up to set email alerts
|

The COVID‐19 pandemic, mask‐wearing, and emotion recognition during late‐childhood

Abstract: Face masks are an effective and important tool to prevent the spread of COVID‐19, including among children. However, occluding parts of the face can impact emotion recognition, which is fundamental to effective social interactions. Social distancing, stress, and changes to routines because of the pandemic have also altered the social landscape of children, with implications for social development. To better understand how social input and context impact emotion recognition, the current study investigated emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 69 publications
0
12
1
Order By: Relevance
“…Compared to adult participants, child participants demonstrated poor performance in emotion recognition from mask-worn faces in a variety of facial expressions. To the best of our knowledge, this is the first study with a sample of East Asian children to test the effects of mask-wearing on reading emotion from a face (Bourke et al, 2023; Carbon & Serrano, 2021; Chester et al, 2022; Cuzzocrea et al, 2023; Gil & Le Bigot, 2023; Giordano et al, 2022; Gori et al, 2021; Ruba & Pollak, 2020; Schneider et al, 2022, for Western children), including studies investigating emotion recognition from parts of the face (Gagnon et al, 2014; Guarnera et al, 2017, 2015; Roberson et al, 2012, for Western children). In addition to identifying the negative influence of wearing masks, we further demonstrated that this impairment in emotion recognition can be alleviated by using a transparent mask.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to adult participants, child participants demonstrated poor performance in emotion recognition from mask-worn faces in a variety of facial expressions. To the best of our knowledge, this is the first study with a sample of East Asian children to test the effects of mask-wearing on reading emotion from a face (Bourke et al, 2023; Carbon & Serrano, 2021; Chester et al, 2022; Cuzzocrea et al, 2023; Gil & Le Bigot, 2023; Giordano et al, 2022; Gori et al, 2021; Ruba & Pollak, 2020; Schneider et al, 2022, for Western children), including studies investigating emotion recognition from parts of the face (Gagnon et al, 2014; Guarnera et al, 2017, 2015; Roberson et al, 2012, for Western children). In addition to identifying the negative influence of wearing masks, we further demonstrated that this impairment in emotion recognition can be alleviated by using a transparent mask.…”
Section: Discussionmentioning
confidence: 99%
“…The negative side effects of wearing masks on reading emotions have been investigated in several studies since the onset of the COVID-19 pandemic (Pavlova & Sokolov, 2022). However, these findings rely heavily on empirical studies with adult participants, with the exception of nine studies (Bourke et al, 2023; Carbon & Serrano, 2021; Chester et al, 2022; Cuzzocrea et al, 2023; Gil & Le Bigot, 2023; Giordano et al, 2022; Gori et al, 2021; Ruba & Pollak, 2020; Schneider et al, 2022). It is questionable whether the results for adult participants can be generalized to school-aged children.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Participants could not respond until the entire clip had played and could not repeat the clip. To test recognition, participants categorized a clip as "sad," "calm," or "scary" by selecting the emotion conveyed in the music using a validated and colored pictorial scale that reduced reliance on verbal/reading ability (Figure S1 in the online supplemental materials; Chester et al, 2023). The response options were on the screen while the participants listened to the clips to remove memory requirements in the task.…”
Section: Music Emotion Listening Taskmentioning
confidence: 99%